The Structural Characteristics and Bioactivity Stability of Cucumaria frondosa Intestines and Ovum Hydrolysates Obtained by Different Proteases - Qiuting Wang; Gongming Wang; Chuyi Liu; Zuli Sun; Ruimin Li; Jiarun Gao; Mingbo Li; Leilei Sun (Marine Drugs, 2023)
The study aimed to investigate the effects of alcalase, papain, flavourzyme, and neutrase on the structural characteristics and bioactivity stability of Cucumaria frondosa intestines and ovum hydrolysates (CFHs). The findings revealed that flavourzyme exhibited the highest hydrolysis rate (51.88% ± 1.87%). At pH 2.0, the solubility of hydrolysate was the lowest across all treatments, while the solubility at other pH levels was over 60%. The primary structures of hydrolysates of different proteases were similar, whereas the surface hydrophobicity of hydrolysates was influenced by the types of proteases used. The hydrolysates produced by different proteases were also analyzed for their absorption peaks and antioxidant activity. The hydrolysates of flavourzyme had β-fold absorption peaks (1637 cm−1), while the neutrase and papain hydrolysates had N-H bending vibrations. The tertiary structure of CFHs was unfolded by different proteases, exposing the aromatic amino acids and red-shifting of the λ-peak of the hydrolysate. The alcalase hydrolysates showed better antioxidant activity in vitro and better surface hydrophobicity than the other hydrolysates. The flavourzyme hydrolysates displayed excellent antioxidant stability and pancreatic lipase inhibitory activity during gastrointestinal digestion, indicating their potential use as antioxidants in the food and pharmaceutical industries.